Nano-MgO as a Solid Base Heterogeneous Nanocatalyst for One Pot Three Component Preparation of Schiff Bases Under Solvent Free Conditions - Naeimi, Hossein; Rabiei, Khadijeh; Rashid, Zahra (Current Organic Chemistry, 2016)
An efficient and convenient nanocrystalline MgO catalyzed one pot preparation of double Schiff bases via solvent free method is described. This protocol was designed through treatment of salicylaldehyde (or furfural) with various aromatic aldehydes and NH4OOCPh to afford double Schiff bases in high purity, excellent yields and short reaction times. These compounds are used as significant ligands that can be coordinated with different transition metal ions in order to be used in various applications like catalysis in organic synthesis. The advantages of this method are availability of starting materials, simplicity of the reaction, easy work up procedure, eco-friendly catalyst, green protocol and purity of products. The products were characterized by physical data and spectroscopic techniques such as; FT-IR, 1H NMR, 13C NMR, C.H.N. and Mass spectra.
Keywords: nano mgo